Peran Komunikasi Bisnis Terhadap Kepuasan Pelanggan dalam Meningkatkan Profit di Sampono Perfumery - Fika Anilda; Sabrina Putri Lestari; Ricky Firmansyah (MUKASI: Jurnal Ilmu Komunikasi, 2023)
The Role of Business Communication on Customer Satisfaction in increasing profits at Sampono Perfumery. This research is to determine the role of customer satisfaction in increasing profits in the company. There are several things that you want to pursue so that this research data is collected properly, with the aim of knowing the development of business communications that are always applied in increasing profits at Sampono perfumery in each of its offline stores. The method used is a qualitative method using data collection techniques or questionnaires. The data that will be generated is the role of business communication on customer satisfaction and convenience such as the location of the offline shampoo store in Cimahi on Jalan Raya Cibabat and the newest offline store in Bandung, precisely Jalan Braga, providing the best and comfortable facilities so that pedestrians who are traveling in the city can visit the store, in the shampoo perfumery shop, they provide free facilities such as massage chairs and free coffee to provide comfort to every visitor who comes, provide good quality products, employees who always give a good attitude towards customers , so that satisfaction can create added value and increase consumer convenience when shopping at Sampono Perfumery and always provide customer loyalty in every problem or consumer complaint against the company so that it can be repaired and improved, so that Sampono Perfumery can further improve the service back at each of each store.